E-Market Electronic Products Using Cross Selling - Abdullah, Abdullah; Megawaty, Megawaty (Universitas Bumigora, 2023)
Background: CV Permata Hijau Delapan is a shop engaged in Electronic sales that has not implemented a strategy on product sales and marketing, this shop has introduced a sales system through social media, but has not used a recommendation system on the website.Objective: To examine the application of cross selling strategies in the e-market of electronic products owned by CV Permata Hijau Delapan.Methods: The system can recommend products that are widely purchased by consumers of CV Permata Hijau Delapan by applying the cross selling method.Result: The system built accommodates the process of sales transactions and product orders online. Survey through google form to customers. It can be seen that the average percentage of each customer satisfaction is towards the product by 65.1%, towards the price by 74%, towards customer service by 75.6%, and towards the shopping experience by 79.8% overall. It can be seen that the dominant customer satisfaction in the survey is towards the shopping experience of 79.8%.Conclusion: This study shows that the implementation of cross-selling strategies in the e-market of electronic products CV Permata Hijau Delapan is efective in increasing sales.